Encounters with peripheral individuals and rural communities for cultural competence development: A case study of learners of Spanish in Colombia - Llanes Sanchez, Juliana Patricia (Colombian Applied Linguistics Journal, 2018)
Cultural competence (Puren, 2013) has been considered a critical aspect for foreign language (FL) teaching and learning due to the wide range of cultural elements associated with the learning of FLs. Hence, this case study aims to describe and understand how encounters with peripheral individuals and rural communities contribute to developing learners’ cultural competence in a Spanish as a foreign language course. The participants were three learners who got involved with peripheral individuals and rural communities as part of a voluntary program included in the syllabi of their course. The current study provides an emic perspective following the research participants’ views and was guided by the principles of qualitative research. Data were gathered from a variety of sources: An online questionnaire, semistructured interviews, classroom observation field notes, and audiotaped social interactions. Content and interpretive analyses were carried out on the data. The findings support the importance of social action and experiential learning for cultural competence development. In addition, the outcomes suggest that the studied encounters not only provided learners with opportunities to enhance knowledge about cultures, but also helped them to encounter otherness and to expand understandings of professional cultures.